A Review On Rheumatic Disease Awareness - Ahmadzai, Mohammad Hanif; Siddiqui, Mohammad Rahman; Chandwani, Jyotsna; Dabi, Sughosh; Kaur, Manveer (Journal of Neonatal Surgery, 2025)
ARF/RHD are conditions associated with low socioeconomic status and insufficient access to healthcare services. Despite their capacity to inflict considerable mortality and morbidity in low-income regions, these preventable diseases frequently receive insufficient attention in developed countries. To tackle the absence of a definitive treatment, it is essential to prioritize prevention and control strategies. It is essential to enhance understanding of the disease and its effects on millions of individuals globally. Thus in this review we have address the awareness and knowledge globally by understanding its epidemiology, importance,barriers and different strategies that can be used for RHD.